Desempenho de concentrados sanguíneos no controle dos sinais e sintomas inflamatórios após a exodontia dos terceiros molares inferiores - Almeida, Vinícius Lima de (2023)
The present study aims to summarize the available evidence and answer the following question: What is the current knowledge on the performance of blood concentrates in handling sequelae after lower third molar extractions with the evidence available in systematic reviews? An electronic search was made in the Cochrane Library, Embase, LILACS, MEDLINE (via PubMed), SciELO, Scopus, and Web of Science databases. The EASY and MedRxiv databases were also used to capture the "grey literature." The study included systematic reviews with or without meta-analyses that investigated the performance of blood concentrates in controlling sequelae after lower third molar extractions. Four outcomes were analyzed: pain, edema, mouth opening, and alveolar osteitis. The AMSTAR-2 tool evaluated the methodological quality of the included systematic reviews, and ROBIS assessed the risk of bias. Among the 388 results, 13 systematic reviews were eligible for the present study. Overall, these reviews evaluated 57 primary studies published from 2007 to 2021, with 30 overlaps of studies selected for the systematic reviews. According to the AMSTAR-2, none of the included systematic reviews presented high or moderate methodological quality. The ROBIS tool showed only one systematic review with a low risk, and the others had a high risk of bias. The limitations of this overview are high heterogeneity and risk of bias in the included systematic reviews and their primary studies, complicating the establishment of correct evidence. However, it is worth noting that the data must be carefully interpreted for clinical decision-making on blood concentrate use, as a detailed analysis showed relevant methodological flaws in apparently robust systematic reviews on the topic. Biological factors pertinent to blood concentrates are promising for optimizing tissue repair, and randomized clinical trials and systematic reviews show inconclusive results regarding the efficacy of these products in controlling sequelae after lower third molar extraction.